Analyzing Key Determinants Of Spotify Adoption: A Structural Equation Modeling Approach Based On The TAM Framework - Krisnadi Geovani Sengkandai; Deske W. Mandagi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
With the growing dominance of digital platforms in the music industry, understanding what drives user adoption and engagement has become increasingly important. This study aims to analyze the key factors influencing the adoption and actual usage of Spotify, a leading global music streaming platform, using the Technology Acceptance Model (TAM) and Structural Equation Modeling (SEM). The research focuses on five core variables: Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, Behavioral Intention to Use, and Actual Use. Data were collected through an online survey of 231 respondents, primarily consisting of younger users, who represent Spotify’s key target demographic. The findings reveal that Perceived Ease of Use significantly affects both Perceived Usefulness and user attitudes toward the app. In turn, Perceived Usefulness fosters more positive attitudes, which increase the intention to use the platform and ultimately lead to actual usage. These results underscore the importance of delivering a seamless and relevant user experience, especially for digital-native users. The study offers practical implications for Spotify and other music streaming services in enhancing competitiveness through personalization, improved usability, and loyalty-driven marketing strategies tailored to younger consumers.